Uma história do pensamento em marketing - Ajzental, Alberto (2008)
The study of a discipline and its history may help in its better understandig, in a deeper and broader sense. Considering a discipline as the accumulation of scientific knowledge in a certain area of thought through an established evolutive process, this academic work intends to establish and presents how Marketing evolved. It’s assumed that the buiding blocks of a discipline are the academic papers published in academic Journals, which are the vehicle of class associations, either those presented in congress, both promoted by class associations representing a school of thought. So far, this academic work presents the evolution of main schools of thought in Marketing, within most representative papers.